2019
DOI: 10.32598/ptj.9.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cognitive Loads on Gait Stability in Younger and Older Adults

Abstract: Purpose: As many older people fall during dual tasks, we aimed to examine the effect of different cognitive loads on learning gait stability in younger and older adults.Methods: 10 younger (Mean±SD age: 25.91±3.42 years) and 10 older adults (Mean±SD: 66.65±4.28 years) were healthy volunteers without a history of falls. They were asked to do three tasks on a treadmill with cognitive load (none, simple, and complex). The Gait-stability Ratio (GSR) was calculated in each condition. Two-way repeated-measures ANOVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The calculation of the GSR (steps/m) was performed by dividing the CAD performance by the GS performance [ 36 ]. Previous studies have shown GS, CAD, and GSR to be auxiliary and effective measures, capable of identifying the mechanisms used by older adults to adjust gait and maintain stable dynamic balance [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of the GSR (steps/m) was performed by dividing the CAD performance by the GS performance [ 36 ]. Previous studies have shown GS, CAD, and GSR to be auxiliary and effective measures, capable of identifying the mechanisms used by older adults to adjust gait and maintain stable dynamic balance [ 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…In turn, a reduction in stride length reflects a decrease in forwarding progression and a consequent increase in time spent supporting both lower limbs [ 43 , 44 ]. Previous studies have highlighted GS, CAD, and GSR as effective measures to assess gait adaptation strategies to maintain balance during challenges [ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%